The Effectiveness Of The Community Social Care Management Program On The Welfare Of The Community Of Sengon Sari Village, Asahan Regency - Nisa Munthe, Ira Hairun; Armayani Hasibuan, Reni Ria; Ikhsan Harahap, Muhammad (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2020)
The Community Social Care Management Program (PPKM) in Sengon Sari Village is an initiative launched to improve community welfare through various social interventions. This program aims to address fundamental problems such as lack of public facilities, health services, education, and community economic conditions. By involving donations from more affluent residents, PPKM focuses on providing assistance to underprivileged communities, including orphans, the elderly, and families in need of educational support. This study evaluates the effectiveness of PPKM by considering five main indicators: community understanding of the program, targeted assistance, timeliness of implementation, achievement of program objectives, and real changes in community life. Data were collected through interviews with the Village Head, PPKM Chair, and village community, and analyzed using NVivo 12 Plus software to identify key themes and patterns in the data. The results showed that although PPKM provided significant benefits in increasing access to education and improving public facilities, there were challenges that needed to be addressed. The main challenges included a lack of community understanding of the program, resistance to change, limited funds, and uneven participation. To address these issues, strategies such as increased socialization, use of local media, and transparency in fund management were implemented. This study recommends expanding socialization methods and increasing community participation to improve program effectiveness. In conclusion, PPKM in Sengon Sari Village has shown great potential in improving community welfare, but the success of this program depends on better understanding, active participation, and effective management. The results of this study are expected to provide a clear picture of PPKM implementation and offer recommendations for future improvements.